A combined heating and power system based on compressed carbon dioxide energy storage with carbon capture: Exploring the technical potential. (15th May 2022) - Xu, Wenpan; Zhao, Pan; Gou, Feifei; Wu, Wenze; Liu, Aijie; Wang, Jiangfeng
Highlights: A cogeneration system based on compressed CO2 energy storage is proposed. The performance analysis with different configurations is executed. The heat transfer process is discussed based on the specific storage medium. The different methods to adjust the ratio of heat to power are compared. Abstract: The development of large-scale energy storage system is of great significance on the construction of future sustainable energy supply system. The compressed carbon dioxide energy storage is one of the most promising technologies. To improve the system output power flexibility and investigate the potential of compressed gas energy storage systems for carbon capture. A combined heating and power system based on compressed carbon dioxide energy storage with carbon capture is proposed in this paper. By establishing the thermodynamic and economic modelling, the heat transfer process of main heat exchangers is analyzed, and the parametric analysis is conducted. Results show that the system power is boosted from 5 MW in basic protype to 16.23 MW in improved configuration accompanied by the energy efficiency promoted from 19.84% to 63.44%. The heating power is 2.86 MW and the mass flow rate of carbon capture is 1.57 kg/s under design conditions. The heat transfer in carbon dioxide phase change process can be realized effectively by employing methanol and water. The improvement of low storage pressure has positive effect on the system output, but the system levelized cost of electricity rises from 8.72 to 10.01 cents/kWh. The heating power is rapidly reduced when the compressor inlet pressure near 7.4 MPa. The heat absorption ratio of carbon dioxide in reheater, which can adjust the ratio of heat to electricity from 17.64% to 63.51%, shows the most powerful influence.